Fostering Social Harmony: A Peace-building Approach to Conflict Resolution and Enhanced Social Skills - Tetep Tetep; Alni Dahlena (AL-ISHLAH: Jurnal Pendidikan, 2024)
Education is the best means of resolving every conflict that arises in human life. Despite the frequent occurrence of conflict and violence among students, it is still regarded as a norm, posing significant danger if left unaddressed. This acceptance can contribute to the development of a deteriorating culture, perpetuating hostility, intolerance, intergenerational violence, and diminishing social character values, particularly within student communities. This study formulates a peace-building-based conflict resolution learning model to instill the values of students' social skills, which is carried out on students through the non-equivalent control group design. Data were collected and processed using experimental procedures. Data analysis techniques were analyzed using design models processed through VOSviewer design software and the SEM (Structural Equation Model) method. Structural Equation Modeling, better known as SEM, has several other names, such as covariance structure analysis), analysis of latent variables, analysis of confirmatory factors and analysis of linear structure relationships. The results of the research show that the peace-building model of conflict resolution learning is effective in improving students' social skills, this is evidenced by the increased students' understanding of conflict resolution and violence that they experience directly or indirectly. Increased collaboration between students in finding solutions to the cases studied shows a better understanding of differences of opinion among students. Increased solidarity in solving problems within the group. Based on this, peacebuilding-based conflict resolution learning is sufficient to make a good contribution to cultivating the values of social skills that can be applied in students' daily lives.